Leadership styles, justice and whistle-blowing intention: testing a mediation model. Issue 4 (10th December 2020) - Gupta, Smita; Bhal, Kanika T.
Abstract : Purpose: This study aims to focus on justice perceptions as the operating mechanism for leadership to impact whistle-blowing intention (WBI). Consequently, it aimed to test the mediating role of justice perception through which ethical leadership (EL) and servant leadership (SL) lead to WBI. Design/methodology/approach: Data were gathered from 136 employees of IT companies in India through a questionnaire survey to test the proposed relationships. Findings: The analysis showed that both EL and SL predict employees' WBI via justice as the mediating mechanism. Research limitations/implications: Formal and informal mechanisms by leaders should focus on ensuring that justice is not only done but also perceived by their subordinates in such a way that just being an ethical or servant leader by itself might not result in pro-social behavior like whistle-blowing. Originality/value: Many studies have shown the effect of SL and EL on outcomes like whistle-blowing; however, this study comprises that justice perception might play a critical mediating role through which both leadership styles impact normative/prosocial behavior like whistleblowing. Understanding the role of leadership and justice perception can offer valuable insights into one's WBI and tendencies, thus increasing the amount of variance in the WBI that researchers can explain.